2022
DOI: 10.1016/j.joca.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, incidence, and progression of radiographic thumb base osteoarthritis in a population-based cohort: the Rotterdam Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a large Dutch population cohort study, 8% of men and 15% of women aged under 60 years were found to have basal thumb OA. The incidence increased to 40% in men and 53% in women by the age of 80 years and older (Teunissen et al., 2022). However, the radiographical appearance of this condition does not define the need for surgical treatment, and only a fraction of these older patients seeks medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a large Dutch population cohort study, 8% of men and 15% of women aged under 60 years were found to have basal thumb OA. The incidence increased to 40% in men and 53% in women by the age of 80 years and older (Teunissen et al., 2022). However, the radiographical appearance of this condition does not define the need for surgical treatment, and only a fraction of these older patients seeks medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Trapeziometacarpal joint (TMJ) osteoarthritis (OA) is a common cause of pain and disability of the hands in postmenopausal women (Dahaghin et al., 2005; Gabay and Gabay, 2013; Gillis et al., 2011; Pellegrini, 2001). Its prevalence in the Dutch population is in the range of 15% to 52% for women and it is positively correlated with age (Teunissen et al., 2022). Numerous surgical techniques have been described for treatment of TMJ OA, including trapeziectomy, trapeziectomy with ligament reconstruction with or without tendon interposition, arthrodesis and total joint arthroplasty (TJA).…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic findings of thumb carpometacarpal joint (CMCJ) osteoarthritis (OA) are commonly found in postmenopausal women, of which more than half of them experienced symptoms such as pain and decreased range of motion in the affected hand [1,2]. In the 1950s, trapeziectomy was the preferred technique due to its predictable postoperative pain relief results [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%